К изучению фауны совок Крыма. II. Подсемейство Agrotinae (Noctuidae, Lepidoptera) - Ключко, З.Ф. (Вестник зоологии, 1968)
On the basis of three year collections and analysis of the data from the literature, 70 species of the Agrotinae subfamily were registrated in the Noctuidae fauna of the 'Crimea. II of them are mentioned for the first time in the Crimea: Ochropleura orientalis AIph., 0. musiva H b., Eugnorisrna fugax T r., Standfussiana dalmata S t g r., -Chersotis alpestris B., Ch. multangula H b., Netrocerocora quadrangula E v., Amathes ditrapezium Schiff., A. triangulum Hfn., Eurois occulta L., Cerastis rubricosa Schif. f. Netrocerocora quadrangula was found first in Europe and Chersotis alpestris — in the Ukraine. In the Crimea the Agrotinae of the Mediterranean-Asian and the European-Asian zoo-geographic groups are predominant.